Diskursus Komunikasi Public Relations dalam Konten YouTube “Kehidupan Talitha Curtis” - Wattimena, Grace Heidy Jane Amanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study analyzes the discourse of public relations communication in the management of messages and impressions presented through the YouTube content